Relationship between body and testicular measurements in young buffalo bulls in Cuba - Almaguer, Yanara; Font, Harold; Cabrera, Suitberto; Arias, Yaritza (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: appropriate selection of sires holds great importance in plans to genetically improve and raise buffalos. Objective: to obtain a statistical model that provides accurate associations between body and testicular measurements intended for selection of Bufalypso breed sires. Methods: measurements of body weight (BW), thoracic perimeter (TP), and scrotal circumference (SC) from 649 buffalos aged 2 to 36 months, were used to obtain the models corresponding to the associations between these traits. The statistical significance of the model and the model’s parameters were evaluated using a one-way analysis of variance. The best-fit model was established by calculating determination coefficients (R2) and mean squared error (SE). Results: the most adequate regression model between thoracic perimeter and body weight was TP = 19.89*BW0.37, with 99% and 0.03 for R2 and, SE, respectively. The best association between scrotal circumference and body weight was obtained with the model SC = 1.13*BW0.51, with values of 89% for R2 and of 0.1 for SE. The model that best expressed the relationship between scrotal circumference and thoracic perimeter was SC = 0.02*TP0.89, with R2 = 89% and SE = 0.01. Conclusion: nonlinear models described better the association between body and testicular measurements than the linear ones. These results suggest that nonlinear models are effective for selecting buffalo sires. Keywords: , . Resumen Palabras clave: circunferencia escrotal, modelación, perímetro torácico, peso corporal, regresión no lineal. Resumo Palavras chave: circunferência escrotal, modelagem, perímetro torácico, peso corporal, regressão nãolinear.